Benjamin de Oliveira: The Black Clown at the White Hall - Ligiéro, José Luiz (Farol, 2021)
The article reports the process of setting up a play about Benjamin de Oliveira, the first black clown to be recognized in the world of whites in Brazil. The son of a slave and a foreman, Benjamin ran away with a circus as a child, and, after successive work, became a clown, playwright, director, actor and circus owner. In addition to the study of the historical and political contexts, the process involved experiencing languages such as circus-theater, clowning, magazine theater, satire and melodrama.